Oxytocin administration is a potential tool for behavioral management in felids - Burkhart, Jessica C.; Heilbronner, Sarah R.; Packer, Craig (Frontiers in Mammal Science, 2023)
Living in a group setting is essential for the health and well-being of social carnivores, however, forming groups of territorial animals can be challenging because of the risk of aggression, injury, and even death. Building tolerance among conspecifics is an important component of behavioural management in both captive and free-ranging settings. Numerous laboratory and clinical studies have implicated oxytocin in the formation of social bonds. Previously, we showed that oxytocin administration reduced social vigilance in African lions. Here, we describe a series of case reports in which oxytocin administration was used to facilitate social bonding in both familiar and unfamiliar conspecific pairs and groups of African lions and tigers. Intranasal oxytocin was administered intermittently for a series of weeks. We hypothesised that the intranasal administration of oxytocin would 1) facilitate the bonding process during introductions of unfamiliar individuals, and 2) increase affiliative behaviours for reconciliation between paired individuals currently experiencing negative social interactions. In all cases, positive social interactions were observed.